ANALISIS KAPASITAS CONVEYOR ROBOT KENDALI PENGANGKUT SAMPAH - Ainurrohish, Fajar (Nozzle : Journal Mechanical Engineering, 2023)
Abstract -- The more advanced the human lifestyle, the more waste is generated. Meanwhile, waste management in Indonesia is not as fast as the production of waste, so that in the end there is a buildup of waste. This robotic garbage transporter is a tool for transporting garbage in rivers, lakes so that garbage in the middle of a lake or river can be transported so that it does not cause blockages in rivers or lakes. Garbage that is taken varies by using a lift system using a conveyor and then stored in the ship's garbage bin. This conveyor is driven by a motor engine and forwarded to a 1:50 gearbox and is designed with a tilt angle of 300. To have a good conveyor performance From the conveyor lift tests that have been carried out, the most optimal capacity is obtained, namely at a conveyor tilt angle of 30⁰ with a motor speed of 4000 RPM with 1:50 gearbox. With a load of 10 kg, the average time is 52.83 seconds, capacity is 656,81 kg/hour, the load is 20 kg, the average time is 53.83 seconds, capacity is 1337,46 kg/hour, the load is 30 kg, the average time is 54.81 seconds, capacity is 1970,44 kg. /hour